The Influence of Work Discipline, Work Environment, and Work Productivity, on Employee Performance at the Youth and Sports Office, Culture and Tourism of Labuhanbatu Regency - Naomi Simarmata; Zulkifli M. Efendi Sir; P. Pristiyono (PT Mattawang Mediatama Solution, 2022)
The aim of this research is to examine the effect of work discipline, work environment, work productivity on employee performance, work discipline has a positive and significant effect on employee performance. To find out the work environment on employee performance has a positive and significant partial effect on employee performance. And also to find out the work productivity of employees has a positive and significant effect on employee performance. To find out work discipline, work environment, work productivity together (simultaneously) have a positive and significant effect on employee performance. The total population of this study were all employees of the Department of Youth and Sports, Culture and Tourism of Labuhanbatu Regency, 70 people by using a saturated sampling technique. The data collection method is using a questionnaire. Data analysis using multiple regression analysis with SPSS software. This study shows the results that: Work discipline, work environment and work productivity together have a positive and significant effect on employee performance. Likewise, Work Discipline, Work Environment and Work Productivity have a positive and significant effect on Employee Performance. The leadership of the Department of Youth and Sports, Culture and Tourism should focus more on aspects of work discipline, work environment and work productivity, in order to provide good and maximum service. Work environment and work productivity together have a positive and significant effect on employee performance. Likewise, Work Discipline, Work Environment and Work Productivity have a positive and significant effect on Employee Performance. The leadership of the Department of Youth and Sports, Culture and Tourism should focus more on aspects of work discipline, work environment and work productivity, in order to provide good and maximum service. Work environment and work productivity together have a positive and significant effect on employee performance. Likewise, Work Discipline, Work Environment and Work Productivity have a positive and significant effect on Employee Performance. The leadership of the Department of Youth and Sports, Culture and Tourism should focus more on aspects of work discipline, work environment and work productivity, in order to provide good and maximum service.